Marketing Strategy Using Promotional Methods to Increase Sales of Aluminum Furniture UD. Mebel Ibu Ida Central Amuntai District - Fitriyatunnisa; Haris Fadillah; Yudianto, Ary (Journal of Business Transformation and Strategy, 2024)
Abstract: This study aims to determine the forms and barriers to marketing strategies using promotional methods to increase sales of Ibu Ida's aluminum furniture in Tapus Village, Central Amuntai District, Hulu Sungai Utara District. This is due to the large number of aluminum furniture craftsmen, and having a place that is not far away, and the decline in the selling price of cabinets while the price of raw materials for furniture is getting more expensive, and the products that are traded are almost the same. So that the craftsmen are competing to do various ways to attract the attention of potential customers by offering their products. The method used in this research is a qualitative research method. In this study, the research location was determined using a purposive sampling system and then a research approach, data analysis and testing the credibility of the data by means of negative case analysis. The results of this study indicate that the marketing strategy using promotional methods in increasing sales of Mrs. Ida's aluminum furniture namely by using social media such as WhatsApp, Facebook, Instagram, and utilizing print media, as well as giving discounts to customers. to doing direct marketing, and retaining loyal customers, and having sales distributors. However, there are some minor obstacles such as barriers to direct marketing, barriers to using social media, obstacles to offline marketing strategies, barriers to differences of opinion, to a lack of trust, and misunderstandings. In the entire study, it can be concluded that Mrs. Ida has adopted several marketing strategies with various promotional methods to increase sales of aluminum furniture in Tapus Village. However, there are still small obstacles that need to be overcome for the marketing strategy to achieve greater success   Keywords: Marketing Strategy, Promotion, Sales